New Pedagogical Technologies in Teaching English - Ortikov Eldor Mardonovich (International Journal on Human-Computing Studies, 2021)
At present, ensuring the quality of teaching the younger generation in foreign languages, radically improving the system of training specialists fluent in foreign languages, training of qualified personnel who meet international educational standards through the acquisition of foreign languages is carried out in our country. is one of the goals of education reform